Does Multimodal Rehabilitation for Ankle Instability Improve Patients' Self-assessed Functional Outcomes? A Network Meta-analysis. Issue 6 (June 2018) - Tsikopoulos, Konstantinos; Mavridis, Dimitris; Georgiannos, Dimitrios; Vasiliadis, Haris S.
Abstract: Background: Although there are many nonsurgical treatment options for the primary management of chronic ankle instability, the most effective nonoperative intervention has not been defined. Questions/purposes: The purpose of this study was to perform a network meta-analysis to compare the results of different standalone and/or combined nonsurgical interventions on chronic ankle instability as measured by (1) the Cumberland Ankle Instability Tool (CAIT) at 0 to 6 months after treatment and (2) treatment-related complications. Methods: We searched PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and Scopus in August 2017 for completed studies published between 2005 and 2016. We conducted random-effects pairwise and network meta-analysis considering randomized trials, which compared the effects of various nonoperative therapies for ankle instability. Studies assessing patients with functional ankle instability and/or mechanical ankle instability and/or recurrent ankle sprains were eligible for inclusion. After combining data from self-administered questionnaires, we analyzed patient self-reported outcomes of function at the end of the rehabilitation period and 1 to 6 months after treatment. We thereafter reexpressed standardized mean differences to mean differences with CAIT. For this instrument, scores vary between 0 and 30, and higher scores indicate better ankle stability. We included 21 trials involving 789 chronically unstable ankles. The rehabilitation interventions included, but were not limited to, balance training, strengthening exercises, a combination of the balance and strengthening exercises, manual therapy, and multimodal treatment. The implemented multistation protocols were targeted at four main areas of rehabilitation (ROM, balance, strength, and overall activity). Control was defined as placebo and/or wait and see. Treatment-related complications were defined as any major or minor adverse event observed after rehabilitation as reported by the source studies. Statistically, we did not detect significant inconsistency in the network meta-analysis. We also assessed the quality of the trials using the Cochrane risk of bias tool and judged 12, eight, and one studies to be at a low, unclear, and high risk of bias, respectively. We also considered the quality of evidence to be of moderate strength utilizing the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. We defined the minimum clinically important difference (MCID) in the CAIT to be 3 points. Results: A 4-week supervised rehabilitation program, which included balance training, strengthening, functional tasks, and ROM exercises, was favored over control according to the results of four trials by a clinically important margin (mean difference between multimodal and control groups in the CAIT was -10; 95% confidence interval [CI], -16 to -3; p = 0.001). Among the standalone interventions, only balance training was better than control according to the findings of seven trials (mean difference between balance training and control in the CAIT was -5; 95% CI, -10 to -0.03; p = 0.049); this difference likewise exceeded the MCID and so is believed to be a clinically important difference. Adverse events associated with the enrolled rehabilitation protocols were transient, mild, and uncommon. Conclusions: Although a supervised impairment-based program after chronic ankle instability was superior to control, we note that followup in the included trials tended to be short and inconsistent, although the effect size exceeded the MCID and so likely would be identified as clinically important by patients. Future randomized trials should determine whether the short-term benefits of these interventions are sustained over time. Level of Evidence: Level I, therapeutic study.